Implementation of Punishment in Forming the Morals of Students of MTS Al-Washliyah, Pakam Village, Medang Deras District, Batu Bara Regency: Implementasi Punishment dalam Membentuk Akhlak Siswa MTS Al-Washliyah Desa Pakam Kec. Medang Deras Kab. Batu Bara - Hasanah, Uswatun; Erlina, Erlina (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The current condition of students' morals can be said to be concerning, and does not recognize age. There have been many incidents of students who do not have good morals. This is proven by the rampant behavior of students that reflects their low morals and ethics. This condition is reflected in inappropriate content that is widely and freely circulated on social media. This study aims to determine the implementation of punishment in shaping the morals of students at MTs Al-Washliyah, Pakam Village, Medang Deras District, Batu Bara Regency. The research method used is qualitative based on phenomenology. The data collection techniques used are observation, interviews, and documentation. The data obtained were then analyzed using the Miles and Huberman techniques, namely data reduction, data presentation, and drawing conclusions. The results of the study explain that the implementation of punishment at MTs Al-Washliyah, Pakam Village has proven effective in shaping better student morals. The punishment applied at MTs Al-Washliyah, Pakam Village shows that punishment can be part of a positive and constructive education and learning process.